Unifying Aleatoric and Epistemic Uncertainty in Investment Evaluation - Bartłomiej GAWEŁ (Communications of International Proceedings, 2025)
In software architecture design, proper attention is often not paid to the relationships between elements across diagrams. However, IT designers, more or less consciously, introduce elements representing the same object instance in different diagrams with nearly identical names. These relationships are called consistency rules and are typically not supported in current software modeling tools. A software architecture without consistency rules is simply an unrelated set of diagrams. Failure to apply consistency rules leads to countless inconsistencies in software architecture. This article presents a mathematical proof demonstrating that applying consistency rules primarily increases the information content of a software architecture. Therefore, the concepts for improving the readability and orderliness of software architecture using consistency rules also have a strong mathematical basis. This article demonstrates the reduction of information entropy (information uncertainty) when applying consistency rules in the design of software architecture of IT systems. It has therefore been proven that labeling selected elements in different diagrams with similar names, indicating the use of consistency rules, is a very effective way to increase the information content of a software architecture while simultaneously improving its orderliness and readability. Considering the constantly increasing quality requirements placed on IT systems, it seems that without IT specialists paying more attention to consistency rules in software development, it will not be possible to significantly improve the current stagnation in software development methods.
Keywords: Entropy; software architecture; software architecture metrics